The influence of work motivation and non-physical work environment on work productivity in Poshbrain Studio employees - Prahmana, Anggi; Tarmidi, Didi (Jurnal Mantik, 2024)
The goal of this study is to find out how non-physical work environments and work motivation affect individual and team productivity, as well as quality and quantity of output.This study's methodology is based on survey responses from 60 Poshbrain Studio employees.With the help of the SPSS 25 data processing system, multiple regression analysis was used to test the impact of work environment and motivation on productivity.The study's findings indicate that Poshbrain Studio employees' productivity at work is influenced by their work environment and workplace motivation.The impact of the work environment and workplace motivation on employee productivity was 45.5%.